Study on the Corrosion Behavior of Rare Earth / Niobium Microalloyed Steels in Marine Atmospheric Environments - ZHANG Xian, HU Hong-yi, GONG Li, WANG Zhi-yuan, PENG Ding, ZHU Chang-jin, WEI Wen-zhui, WU Kai-ming (Cailiao Baohu, 2021)
For providing the data support to design and develop microalloyzed steels, the corrosion behavior of rare earth microalloyed steels and niobium microalloyed steels in marine atmospheric environments was investigated by the means of surface microstructure characterization, alternative wet/dry cycle test, neutral salt spray test and electrochemical measurements.Furthermore, the corrosion resistance of microalloyed steels was compared and analyzed.Results showed that the microstructure of microalloyed steels consisted of ferrite and pearlite, and niobium microalloying favored the refinements of the grains and hindered the formation of pearlite.The rust layer was composed of for γ-Fe2O3 and γ-FeOOH, which had no obvious protective effect to the substrate.With prolonging exposure periods, γ-FeOOH gradually transformed to α-FeOOH, enhancing the protective effect to the substrate.The corrosion current density of rare earth/niobium microalloyed steels declined, and thus the corrosion resistance of those two kinds of steels were improved.After a long period of corrosion, the grain refinement of niobium microalloyed steel was beneficial to increase the densification of the surface rust layer and the content of α-FeOOH was relatively high, then further the corrosion rate was reduced.Hence, compared with rare earth microalloyzed steel, the niobium microalloyed steels presented a better atmospheric corrosion resistance.